An evaluation of the SF-36 questionnaire in patients with gouty arthritis - Folatova, A.A.; Utkurova, K.A.; Tashpulatova, M.M. (Science and Education, 2023)
Objective: to assess quality of life (QL) of gouty patients by SF-36 questionnaire in comparison with standardized indicators of population-based control. Subjects and methods: The study included 198 patients with gout, in each case the diagnosis was verified by detection of crystals of monosodium urate. The patients’ mean age was 46.5 ± 2.5 years (24 to 68 years); the median disease duration was 4 years. The SF-36 questionnaire was used to compare the quality of life of the patients with the standardized indicators of the population. The comparison was made separately in different age groups: 24-34 years (n = 48), 35-44 years (n = 50), 45-54 years (n = 49), 55-68 years (n = 51). Results: According to the scales of physical functioning, role physical functioning, intensity of pain and general state of health, values of QL ​​were 5-8 points lower than population-based control (p <0.0001). The average standardized indicators of viability (p <0.0005) and social functioning (p <0.02) were also lower than the population ones and indicated a limitation of vital activity and social contacts. Comparative analysis revealed the above-mentioned similar differences in different age groups. For age groups older than 35 years, there was no difference in any of the indicators characterizing psychological health. Only in the group from 24 to 34 years with gout, we found lower values ​​of psychological health than population, on the scale of social functioning, which was also demonstrated when comparing the general group of patients with gout with population control not divided into age groups. Conclusion: The physical health of the gouty patients is mainly poor and their mental health is poor to a lesser degree; their social adaptation is decreased.